Manajemen Gereja dengan Balanced Scorecard untuk Peningkatan Kinerja Pelayanan Gereja - Kusbianto, Agus; Jahja, Sundoro; Gidion, Gidion (P3M STT Kristus Alfa Omega, 2025)
Measuring service performance is crucial for a church as a religious organization. In the business world, service performance measurement typically uses a balanced scorecard (BCS), which can also be used within the church. The Full Gospel Fellowship International Church in Plamongan Indah, Semarang, has been using a balanced scorecard (BCS) for some time, but the results have not been satisfactory. Therefore, it is necessary to develop a balanced scorecard (BCS) design to improve the church's service performance. This study, which uses the Sequential Explanatory Mixed Method, produces a strategy map with ten interconnected strategic objectives from the four perspectives of the balanced scorecard (BCS). The ten strategic objectives consist of two strategic objectives from the financial perspective, two strategic objectives from the customer perspective, three strategic objectives from the internal business process perspective, and three strategic objectives from the learning and growth perspective. Through these ten strategic objectives, a church can apply them in planning, implementing and evaluating the performance of church services periodically to be able to continue to experience improvements.